1995
DOI: 10.1159/000292386
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma Endothelin Levels and Fetal Status in Normal and Preeclamptic Pregnancies

Abstract: Endothelin (ET) is a potent vasoconstrictor peptide. In this study, we investigated maternal venous plasma ET levels measured by Sandwich-enzyme immunoassay within a week before the onset of labor, and measured plasma renin activity and plasma aldosterone concentration by radioimmunoassay in normal and severely preeclamptic pregnancies. Also, we determined umbilical cord blood pH and gas concentrations after spontaneous vaginal deliveries and cesarean sections. There was a significant (p < 0.01) negative corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…ET‐1 has been suggested to play a role in pre‐eclampsia (Maynard et al ., ). ET‐1 levels are increased in pre‐eclampsia, particularly when accompanied with intrauterine growth restriction (McQeen et al ., ; Furuhashi et al ., ), and modulation of the ET‐1 system may be an important target in the management of pre‐eclampsia. Studies have shown that infusion of ET A R antagonist reduces BP in the L‐NAME‐infused reduced uterine perfusion pressure and sFlt‐1‐infused rat models of hypertension in pregnancy (Olson et al ., ; Alexander et al ., ; Murphy et al ., 2010; 2012; Tam Tam et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…ET‐1 has been suggested to play a role in pre‐eclampsia (Maynard et al ., ). ET‐1 levels are increased in pre‐eclampsia, particularly when accompanied with intrauterine growth restriction (McQeen et al ., ; Furuhashi et al ., ), and modulation of the ET‐1 system may be an important target in the management of pre‐eclampsia. Studies have shown that infusion of ET A R antagonist reduces BP in the L‐NAME‐infused reduced uterine perfusion pressure and sFlt‐1‐infused rat models of hypertension in pregnancy (Olson et al ., ; Alexander et al ., ; Murphy et al ., 2010; 2012; Tam Tam et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to measure circulating levels of ET-1, NO x , sFlt-1, and PlGF given previous studies showing their importance in relation to the occurrence of fetal growth restriction and preeclampsia (1,7,8,17,18,25). For example, ET-1 is a potent vasoconstrictor that is known to be elevated in pregnancies complicated by preeclampsia or SGA (7,8), and when its vasoconstrictor actions are inhibited with the use of ET-1 antagonists, hypoxia-associated reductions in uteroplacental blood flow and fetal growth in rat models are completely abolished (27). In this study, ET-1 levels were not elevated at high relative to low altitude during pregnancy or in the nonpregnant state.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1, a well known potent vasoconstrictor, may be involved in the pathogenesis of hypertension in pregnancy [14,15]. The relationship between insulin and ET-1 is not clear.…”
Section: Discussionmentioning
confidence: 99%